Amount of carbon sequestration distribution associated with oak tree’s (Quercus castaneifolia C.A. May) bole in relation to physiographical units of Hyrcanian natural forests of Iran - Ali Asghar Vahedi; Asadollah Mattagi (تحقیقات جنگل و صنوبر ایران, 2014)
Carbon sequestration rate of forest trees and their spatial pattern are prominent factors which affect global carbon dynamic and can be basically applied to predict climate change. For this reason, compartments2 and 4 of district3 of Glandrood Forest were selected for this study and few disks (2 cm thick) were sampled from each felled oak tree at 2-5 m. interval of its bole. Further samplings were made from each disk at constant volumes (3x3x3 cm) and intervals (2 cm). The samples were oven dried in lab for 24 hours (105°C) in order to determine their dry density. Carbon factor was obtained directly by exposing the wood samples in the oven and was estimated, based on organic carbon/organic material ratio. Compartment3 of district3 (38 hectares) was selected as a control due to its undisturbed and virgin characteristics, to determine carbon sequestration of the oak trees and their spatial pattern in relation to the physiographical units. After that, 400 m2 sampling plots were allocated in the compartment, using the random systematic method at 100 m. grids, then diameter at breast height and total height of the aimed trees were measured. Carbon sequestration was estimated, using the volume x dry density x carbon ratio equation. The results of one-way Anova analysis showed that although there was significant difference between the dry wood density values at different intervals, with respect to pith to periphery (bark) of cross-section of disks (P < 0.01), but there was no significant difference between the individual oak trees at different diameter dimensions (P > 0.05). As the average value of oak wood dry density is 0.81± 0.0083 g.cm-3 and average carbon factor is % 57.37 ± 0.108, so according to the results of Paired-Samples t test, the values of calculated carbon sequestration were significantly more than the estimated values (P < 0.01) and their difference was 4.267 ± 1.39 t / ha. Overall, the result of one-way Anova analysis showed that there was not significant difference among the carbon sequestration values of the oak trees at various physiographical units (P >0.05) which indicates that the spatial pattern of carbon sequestration values in the oak bole trees at the aimed study area were not  associated with the environmental physical affects.